Proceedings of International Conference on Making Sense of Converging Media 2013
DOI: 10.1145/2523429.2523474
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Gesture Recognition Technology in Children's Interactive Storybook

Abstract: Technological development has significantly affected children's everyday life over the last decades. Interactive technologies have become an inseparable part of their daily lives. In this paper, we present the results of a case study of product designs that aims to provide new opportunities for children to enjoy traditional storybook, more interactive fashion. Also, the aim was to increase understanding about full-body gesture technology when users are young children. The initial prototype of the Kinetic Stori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…However, they presented some concerns regarding the adoption of the tool. Although the use of Kinect in classes was explored in other works (Shiratuddin and Wong 2011;Kauppinen et al 2013;Renzi et al 2015), our results showed that the number of students to deal with could impact negatively in the acceptance of technology by the teachers. The teachers' statements reinforce the results found out in the literature that the NUI acts positively on the attention and the engagement of the children for the use of learning tools (Goyal et al 2017;Rahman et al 2013;Falcão et al 2017;Martin-SanJose et al 2017).…”
Section: Findings and Discussion On The Teachers' Perspectivementioning
confidence: 61%
See 3 more Smart Citations
“…However, they presented some concerns regarding the adoption of the tool. Although the use of Kinect in classes was explored in other works (Shiratuddin and Wong 2011;Kauppinen et al 2013;Renzi et al 2015), our results showed that the number of students to deal with could impact negatively in the acceptance of technology by the teachers. The teachers' statements reinforce the results found out in the literature that the NUI acts positively on the attention and the engagement of the children for the use of learning tools (Goyal et al 2017;Rahman et al 2013;Falcão et al 2017;Martin-SanJose et al 2017).…”
Section: Findings and Discussion On The Teachers' Perspectivementioning
confidence: 61%
“…Body movements, gestures and voice are recognized as NUIs, because they represent movements and actions that humans usually do in the real world (Rahman et al 2013;Wigdor and Wixon 2011). However, the so-called natural movements are not always understood in this way by children (Kauppinen et al 2013), which can cause a misunderstanding of how children face the interaction and the learning goal.…”
Section: Fundamentalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Estudos têm sido desenvolvidos para mostrar o potencial do uso das mãos em aplicações voltadas à aprendizagem. Kauppinen et al (2013) apresentam um estudo utilizando a aplicação Kinect Stories, onde crianças de 3 a 6 anos interagem com um livro de histórias, utilizando gesto e comandos por voz. Renzi et al (2015) utilizaram NUI e gestos para estimular e motivar as crianças a aprender o básico sobre notação musical.…”
Section: Trabalhos Relacionadosunclassified